Optimizing Wnt activation in fetal calf serum (FCS)-free organoid expansion media - Liefting, Esther J. M.; Bajramovic, Jeffrey J. (Frontiers in Toxicology, 2025)
Organoid technology can revolutionize biomedical research by increasing the translational value of experimental results while at the same time reducing the need for experimental animal use. However, in most cases the organoid culture workflow relies on expansion media that contain fetal calf serum (FCS). The production of FCS causes animal suffering, and the use of it is hampered by factors that negatively impact the reproducibility (such as the large inter-batch variation and the undefined composition of FCS), relevance (such as the induction of a non-physiological cellular phenotype), as well as the clinical translatability (such as the potential to cause xeno-immunization or to contain xenogeneic pathogens). There is thus a strong impetus to find animal-free alternatives to the use of FCS. Most contemporary expansion media for organoid culture are not FCS-free. This is mainly contributable to the use of FCS for the recombinant production of the growth factor Wnt3A. Wnt3A-conditioned medium is added to expansion media to induce Wnt signaling, which is necessary for organoid proliferation. In turn, FCS is pivotal to stabilize and solubilize the Wnt3A protein, and not perse for the survival, adhesion or proliferation of cells. This mini-review explores alternative methods to induce Wnt signaling in organoid expansion media, encompassing the use of soluble Wnt mimetics, the use of carriers, and the use of small molecule inhibitors. Ultimately, alternative Wnt activation approaches for different experimental goals are reviewed and discussed.